Five new grasses from colombia (1943)
The new species herein described, of Sporobolus, Calamagrostis, and Agrostis, are based on recent collections of J. Cuatrecasas and H. Garcia-Barriga, and the new Panicum on collections of F. W. Pennell and E. P. Killip, and of H. Garcia-Barriga. The new Isachne was first collected in 1922 by F. W. Pennell and E. P. Killip in the Cauca Valley and has since been found a number of times in adjo-ining Departmerits.